2009
DOI: 10.4184/asj.2009.3.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Levels of Lumbar Spondylolysis - A Case Report -

Abstract: We report here on an unusual case of multiple levels of asymmetric lumbar spondylolysis in a 19-year-old woman. The patient had severe low back pain of increasing intensity with lumbar instability, which was evident on the dynamic radiographs. MRI demonstrated the presence of abnormalities and the three dimensional CT scan revealed asymmetric complete spondylolysis at the left L2, L3 and L4 levels and the right L1, L2 and L3 levels. This case was treated surgically by posterior and posterolateral fusion at L2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
2
10
0
1
Order By: Relevance
“…According to Kwang-Hwan Park et al, the incidence of multiple lumbar spondylolysis appears to vary between 1.2% to 5.6%. [10,11] In our study, multilevel spondylolysis was seen in 1.8%.…”
Section: Discussionsupporting
confidence: 45%
“…According to Kwang-Hwan Park et al, the incidence of multiple lumbar spondylolysis appears to vary between 1.2% to 5.6%. [10,11] In our study, multilevel spondylolysis was seen in 1.8%.…”
Section: Discussionsupporting
confidence: 45%
“…If lumbar spondylolysis occurs in adolescents, conservative treatment is usually the first choice[ 8 ]. Clinical observation found that new onset spondylolysis may be cured by restricting lumbar spine movement with a brace[ 2 , 5 , 9 , 10 ]. A retrospective study showed that a union rate of conservative treatment in adolescents was 76%[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Мы обнаружили 14 публикаций зарубежных авторов, описывающих клинические случаи многоуровневого спондилолиза в общей сложности у 21 пациента различного возраста. При этом публикации 12 исследователей посвящены описанию всего лишь одного клинического случая патологии [2,16,23,28,39,45,65,73,74,[78][79][80]. Еще по одному автору описывают течение изучаемой патологии у пяти [70] и трех [18] Отдельно следует выделить клинические наблюдения c. Zhang с соавторами за 9 пациентами, у каждого из которых был диагностирован спондилолиз поясничных позвонков на двух уровнях и, как следствие, сформировавшийся на этих же уровнях спондилолистез.…”
Section: материал и методыunclassified